In vivo multi‐tissue efficacy of peroxisome proliferator‐activated receptor‐γ therapy on glucose and fatty acid metabolism in obese type 2 diabetic rats. (31st May 2013) - Nemanich, Samuel; Rani, Sudheer; Shoghi, Kooresh
<x xml:space="preserve">Abstract</x> Objective To identify the disturbances in glucose and lipid metabolism observed in type 2 diabetes mellitus, we examined the interaction and contribution of multiple tissues (liver, heart, muscle, and brown adipose tissue) and monitored the effects of the Peroxisome Proliferator‐Activated Receptor‐γ (PPARγ) agonist rosiglitazone (RGZ) on metabolism in these tissues. Design and Methods Rates of [18F]fluorodeoxyglucose ([18F]FDG) and [11C]Palmitate uptake and utilization in the Zucker diabetic fatty (ZDF) rat were quantified using noninvasive positron emission tomography imaging and quantitative modeling in comparison to lean Zucker rats. Furthermore, we studied two separate groups of RGZ‐treated and untreated ZDF rats. Results Glucose uptake is impaired in ZDF brown fat, muscle, and heart tissues compared to leans, while RGZ treatment increased glucose uptake compared to untreated ZDF rats. Fatty acid (FA) uptake decreased, but FA flux increased in brown fat and skeletal muscle of ZDF rats. RGZ treatment increased uptake of FA in brown fat but decreased uptake and utilization in liver, muscle, and heart. Conclusion Our data indicate tissue‐specific mechanisms for glucose and FA disposal as well as differential action of insulin‐sensitizing drugs to normalize substrate handling and highlight the role that preclinical imaging may play in screening drugs for obesity and diabetes.